Nerve and Vascular Biomarkers in Skin Biopsies Differentiate Painful From Painless Peripheral Neuropathy in Type 2 Diabetes - Shillo, Pallai; Yiangou, Yiangos; Donatien, Philippe; Greig, Marni; Selvarajah, Dinesh; Wilkinson, Iain D.; Anand, Praveen; Tesfaye, Solomon (Frontiers in Pain Research, 2021)
Painful diabetic peripheral neuropathy (painful-DPN) can be intractable with major impact, yet the underlying pain mechanisms remain uncertain. A range of neuronal and vascular biomarkers were investigated in painful‐DPN and painless‐DPN and used to differentiate painful-DPN from painless-DPN. Skin biopsies were collected from 61 patients with type 2 diabetes (T2D), and from 19 healthy volunteers (HV). All subjects underwent detailed clinical and neurophysiological assessments; based on the neuropathy composite score of the lower limbs [NIS(LL)] plus 7 tests, the T2Dsubjects were subsequently divided into three groups: painful-DPN (n=23), painless-DPN (n=19) and No-DPN (n=19). All subjects underwent punch skin biopsy, and immunohistochemistry used to quantify total IENF with protein gene product 9.5 (PGP9.5), regenerating nerve fibres with growth-associated protein 43 (GAP43), peptidergic nerve fibres with calcitonin gene related peptide (CGRP), and blood vessels with von Willebrand Factor (vWF). IENF density was severely decreased (p<0.001) in both DPN groups, with no differences for PGP9.5, GAP43, CGRP, or GAP43/PGP9.5 ratios. There was significant increase of blood vessel (vWF) density in painless‐DPN and No‐DPN groups compared to the HV group, but this was markedly greater in the painful‐DPN group, and significantly higher than in the painless‐DPN group (p< 0.0001). The ratio of sub-epidermal nerve fibre (SENF) density of CGRP:vWF showed a significant decrease in painful-DPN vs. painless-DPN (p=0.014). In T2D patients with advanced DPN, increased dermal vasculature and its ratio to nociceptors may differentiate painful-DPN from painless-DPN. We hypothesize that hypoxia-induced increase of blood vessels, which secrete algogenic substances including nerve growth factor (NGF), may expose their associated nociceptor fibres to relative excess of algogens, thus leading to painful-DPN